AN EVALUATION OF THE SOCIO-ECONOMIC PROFILE AND PERCEPTION OF PERI-URBAN FARMERS: A STUDY IN THE PERIPHERY OF HYDERABAD METROPOLITAN REGION - SEEMA; K. SUPRIYA, JUDY THOMAS, R. VIJAYAKUMARI, S. NEDUMARAN, T. LAVANYA (The Journal of Research, PJTSAU, 2023)
Farm diversification is emerging as an adaptive strategy among the farmers especially those near to the city centers, as availability of land for cultivation is under question with the expanse of developmental activities. The present study was conducted in the peripheries of Hyderabad Metropolitan Region in the year 2021 to assess the socio-economic profile of farm households. A multistage random sampling method was chosen for sampling by which a total of eight mandals were surveyed using a pre-tested structured interview schedule totaling the sample size to 330. The study purely depends on primary data and relevant descriptive statistics were employed for analysis. The socio-economic variables selected for the study include age, education, experience in farming, operational land holding, crop diversity index and income only from agriculture. It was observed that diversified farmers were younger than non-diversified group while level of education was more or less same for both the groups. Farmers with more experience tend to specialize their farmland as against those who diversify even when farming experience is low. In addition, with the increase in landholding size, farmers tend to diversify their farm activities more. While considering the variable only farm as source of income, it was observed that majority of diversified farmers depend on farm alone than non-diversified farmers. Additionally, the perception of peri-urban inhabitants on the social and economic impacts of urban sprawl on their locations was also assessed using Garrett Ranking Technique. Policies should be formulated to support smallholders to pool their land so that they could take up diversification activities profitably.